Optimal income taxation : outsourcing and policy cooperation in a dynamic economy - Thomas Aronsson; Erkki Koskela (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper concerns optimal income taxation in a two-country OLG economy, where each country is characterized by asymmetric information between the government and the private sector, and where one of the countries outsources part of its production to the other. In the country whose firms outsource production abroad, the government will respond to outsourcing by implementing a more progressive labor income tax structure and higher marginal capital income tax rates than it would have done in the absence of outsourcing. The tax policy response by the government in the country that receives foreign production capacity is, in general, ambiguous and depends on a tradeoff between wage-equality and factor income from abroad. By using the noncooperative Nash equilibrium as a reference case, we also consider tax policy cooperation leading to higher welfare.
Keywords: H21; H25; J31; J62; 330; outsourcing; redistribution; optimal nonlinear taxation; intertemporal model; Optimale Besteuerung; Einkommensteuer; Outsourcing; Overlapping Generations; Zwei-Länder-Modell; Theorie